Branded fitness: Exercise and promotional culture. (November 2017) - Powers, Devon; Greenwell, DM
This article develops a theory of branded fitness within the United States through a focus on two of its most visible examples: CrossFit and Bikram yoga. We argue that highly successful forms of branded fitness such as these give insight into the enormous power and permeation of branded sensibilities into everyday life – in this case, going so far as to inform how we relate to, and attempt to modify, our own bodies. However, we argue that a close examination of branded fitness likewise reveals the inconsistencies, trouble spots, and extraordinary limits of the brand as a way to build a fitness movement – which we contend is instructive in thinking about how branding more generally relates to mediation, community, and cultural commodification.